Environmental constraints, biological growth and fleet dynamics of a developing fishery: A model study of the Barents Sea snow crab (Chionoecetes opilio, Majidae) fishery. Issue 2 (7th November 2021) - Hogrenning, Egil; Eide, Arne
Abstract: The snow crab ( Chionoecetes opilio, Majidae) has recently entered the Barents Sea, and a crab fishery is developing. Information on how the crab appeared and where it is moving is limited. We study how the characteristics of the fleet may affect the further development of the fishery. A spatial model is constructed as a grid of cells given a carrying capacity for crab determined by environmental data, assumed to reflect crabs' preferences. The biological dynamics are modelled using cellular automata, describing the growth and movements of the crabs. The fleet dynamics is represented by scenarios of fleet behaviour and aptitude, using standard theories of harvest production and economics. Pattern‐oriented modelling is used to calibrate the model. The fishery started in the Loophole, but is anticipated to expand as the crabs populate adjacent areas. We use simulations to explore a potential geographical expansion of the fishery. The fleet is assumed to continually expand the current fishing area by initiating fishing in adjacent areas, relying only on their own judgement to locate promising fishing grounds. We find an inability to successfully quantify the amount of crabs in the areas subject to exploration and the willingness to take risks to be two forces contributing to a long‐term utilization of the stock. Both forces appear to make the fishers explore non‐lucrative grounds, potentially leading them to lucrative grounds. However, information from other sources indicating the presence of crabs at various locations appears to be necessary to ensure a more complete exploration of the fishery.